Image registration between MRI and spot mammograms for X-ray guided stereotactic breast biopsy - Said, Sarah (KIT Scientific Publishing, 2024)
This work proposes a novel method for a matching tool between MRI and spot mammograms. Two registration methods are used : a biomechanical model based registration between MRI and full X-ray mammograms, followed by an image based registration between full and spot mammograms. The proposed methods have been tested using 51 patients from the Medical University of Vienna. For the analyzed dataset, the proposed methods showed not only promising results but also the feasibility of clinical use.